Treatment strategies for patients with decompensated liver cirrhosis due to hepatitis C virus infection eligible for liver transplantation: real-life data from five German transplant centers - Sandmann, Lisa; Dörge, Petra; Wranke, Anika; Vermehren, Johannes; Welzel, Tania; Berg, Christoph; Grottenthaler, Julia; Weiss, Karl Heinz; Langel, Jessica; Sterneck, Martina; Wulffen, Moritz von; Manns, Michael; et al. (European journal of gastroenterology & hepatology, 2019)
BackgroundEven with highly effective direct-acting antivirals (DAAs) treatment of patients with decompensated hepatitis C (HCV) cirrhosis remains challenging. Clinical deterioration and the need for liver transplantation (LT) may arise despite previous antiviral treatment. It is unclear whether in p
Gesehen am 24.01.2020